Meningkatkan Profesionalisme Pelayanan Publik melalui Penerapan Etika Administrasi di Dinas Sosial Provinsi Sumatera Barat - Afrina Welni; Miken Wulandari; Yunita Yunita; Randy Wilyan Putra; Yulia Hanoselina; Rahmadhona Fitri Helmi (Lembaga Pengembangan Kinerja Dosen, 2024)
This study investigates the use of administrative ethics to increase the professionalism of public services in the West Sumatra Provincial Government Social Service. Data was collected through in-depth interviews with stakeholders and surveys of staff and service users using mixed methods (qualitative and quantitative). Research shows that the application of administrative ethics principles such as transparency, accountability and fairness significantly increases the professionalism of the apparatus and the quality of public services. Integrity, public trust, and operational efficiency of agencies can be strengthened by a strong ethical culture. In addition, this research found that continuous training, improving operational standards, and the use of information technology can help overcome problems such as employees' lack of understanding of administrative ethics and weaknesses in supervisory systems. Policy recommendations are made to encourage public services that are more responsive, professional and in line with community expectations.